Factores de riesgos ambientales y su incidencia en el asma en adultos mayores del barrio Cristo del Consuelo Babahoyo – Los Ríos octubre 2018 – abril 2019 - Carpio Guerrero, Leonel Benito (2019)
Hj Asthma is a chronic inflammatory disease accompanied by acute crisis and persistent symptoms that in many cases is poorly controlled; Current evidence supports that environmental factors are direct intervenors in the worsening of the disease. In such a way that the facts for the disease to worsen depends in large part on environmental irritants, which we must try to avoid considering the respective control measures. In this sense, the objective of this research was to determine the incidence of environmental risk factors in asthma in older adults in the Cristo del Consuelo Babahoyo - Los Rios neighborhood, which was determined with the qualitative and quantitative research modalities used. which concluded that the environmental risk factors affect the asthma of the elderly; this was evidenced by the research instruments carried out that both variables are related. Consequently, an alternative proposal called "Action plan for the prevention and effective control of asthma in older adults in the neighborhood of Cristo del Consuelo Babahoyo - Los Ríos" is proposed. With three fundamental axes such as patient education, avoidance or control measures and asthma control techniques; each of them contains activities that seek to mitigate the disease or try to prevent the onset of symptoms and a crisis once the disease has been established; and that the older adults of the neighborhood also improve their quality of life; and that they have above all the capacity to decide, contextualize in an urgent situation and, above all, adapt what they have learned in the face of adverse situations. The action plan is not a static model, but must evolve and improve according to the needs of people with asthma taking into consideration the different measures of prevention and treatment.